Mokslotyra, informatika ir kai kurie sveikatos apsaugos klausimai - Januškevičius, Zigmas; Vaitkevičius, Kostas (Knygotyra, 1974)
The development of health service and medicine is determined by general laws of the development of science, e. g. by the laws of heredity, internationality and unity. Therefore, studying some questions of practical and theoretical health service, considerable benefit may be derived from the application of ideas of methodological aspects of the general theory of science. It helps to understand some of the difficulties, arising before the health services and medicine as a result of an exponential growth of science and information and of differentiation and integration of medical aid. A scrutiny of these problems from the point of view of the dialectical unity and of the theory of science provides an opporunity to outline some ways of overcoming the difficulties.